The Psychometric Properties of the Edinburgh Postnatal Depression Scale (EPDS) for Depression Screening in Pregnant and Postpartum Women: A Systematic Review - Haris Petriano; Retno Lestari; Heni Dwi Windarwati (Indigenous: Jurnal Ilmiah Psikologi, 2025)
Background: Depression is a major mental health disorder with a significant global impact. Early detection through valid and reliable screening instruments, such as the Edinburgh Postnatal Depression Scale (EPDS), plays a crucial role in its prevention and management. Objective: This review aims to evaluate the psychometric properties of the EPDS, focusing on its reliability and validity in detecting depressive symptoms. Methods: This study is a systematic review of scientific articles identified through three major databases: ScienceDirect, PubMed, and ProQuest. The literature search covered publications from 2021 to 2025 using a combination of the keywords “Depression,” “Edinburgh Postnatal Depression Scale,” “Mental Health,” “Psychometrics,” “Postpartum,” and “Pregnancy,” with Boolean operators AND and OR to retrieve studies relevant to the validity and reliability of EPDS. Article selection was conducted using the PRISMA framework, with predefined inclusion and exclusion criteria. From a total of 337 articles identified, 20 were selected for further analysis. Results: The findings indicate that the EPDS demonstrates good internal reliability and adequate validity in detecting depressive symptoms. Conclusion: EPDS is a reliable screening instrument for detecting perinatal depression, with its consistency maintained through linguistic and cultural adaptations